Exploring Restorative Justice in Domestic Violence Cases - Widiartana, Gregorius; Vincentius Patria Setyawan; Ariesta Wibisono Anditya (Lembaga Contrarius Indonesia, 2025)
The Indonesian government has actively developed restorative justice policies for criminal cases through various laws and regulations; however, their implementation in domestic violence cases remains limited due to the predominance of a retributive mindset among law enforcement officials. In contrast, Malaysia has adopted restorative approaches to address domestic violence through community-based and victim-centered interventions. This research seeks to formulate comprehensive arguments supporting the implementation of restorative justice in domestic violence cases by analyzing relevant legal provisions, doctrinal foundations, and theoretical perspectives, while incorporating a comparative analysis of the Malaysian model. The comparative legal study between Indonesia and Malaysia is particularly significant within the broader framework of legal globalization, ASEAN regional integration, and bilateral cooperation in the fields of law and governance. Both countries, which share an Islamic cultural foundation and a colonial legal heritage, offer compelling contexts for examining the adaptation of restorative justice principles in plural legal systems. In Malaysia, Islamic law regulates various domains of social life, especially in matters of civil and family law, including marriage, divorce, inheritance, and waqf, shaping the socio-legal environment within which domestic violence is addressed. The findings indicate that Indonesia has initiated the application of restorative justice in certain domestic violence cases through mechanisms such as community mediation and police-facilitated reconciliation, though these practices remain inconsistent and are often influenced by patriarchal cultural norms. Conversely, Malaysia maintains a more formal and legalistic approach, with minimal formal recognition of restorative justice within its domestic violence legislation. The study concludes that restorative justice possesses substantial potential as a complementary framework to formal legal remedies, provided that its implementation ensures the protection of victims’ rights, prevents coercion, and upholds fundamental principles of justice, gender equality, and human dignity.